2015
DOI: 10.17795/acr-28794
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Oncologic Short Term Results of Laparoscopic Versus Open Surgery of Rectal Cancer

Abstract: Background: Today, with improvements in laparoscopy technique, surgery of rectal cancer is performed by laparoscopy. Objectives: This study was performed to evaluate oncologic results of open versus laparoscopic surgery of rectal cancer in terms of resection margins, removal of lymph nodes and recurrence rate. Patients and Methods: This descriptive-analytic study was performed on 88 patients with middle and lower rectal cancer in the two equivalent groups of laparoscopic and open surgery in Mashhad Ghaem and O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…However, the histo-pathological findings would not have been significantly affected, as the pathologists who examined the specimens were not aware whether the operation was open or laparoscopic. A few previous studies have shown that the mean number of harvested lymph nodes was significantly higher in laparoscopic than in open surgery [7][8][9]. Our findings are similar to theirs.…”
Section: Discussionsupporting
confidence: 91%
“…However, the histo-pathological findings would not have been significantly affected, as the pathologists who examined the specimens were not aware whether the operation was open or laparoscopic. A few previous studies have shown that the mean number of harvested lymph nodes was significantly higher in laparoscopic than in open surgery [7][8][9]. Our findings are similar to theirs.…”
Section: Discussionsupporting
confidence: 91%